Down-Regulation of OsSPX1 Causes High Sensitivity to Cold and Oxidative Stresses in Rice Seedlings - Wang, Chunchao (Public Library of Science, 2013)
Rice SPX domain gene, OsSPX1, plays an important role in the phosphate (Pi) signaling network. Our previous work showed that constitutive overexpression of OsSPX1 in tobacco and Arabidopsis plants improved cold tolerance while also decreasing total leaf Pi. In the present study, we generated rice antisense and sense transgenic lines of OsSPX1 and found that down-regulation of OsSPX1 caused high sensitivity to cold and oxidative stresses in rice seedlings. Compared to wild-type and OsSPX1-sense transgenic lines, more hydrogen peroxide accumulated in seedling leaves of OsSPX1-antisense transgenic lines for controls, cold and methyl viologen (MV) treatments. Glutathione as a ROS scavenger could protect the antisense transgenic lines from cold and MV stress. Rice whole genome GeneChip analysis showed that some oxidative-stress marker genes (e.g. glutathione S-transferase and P450s) and Pi-signaling pathway related genes (e.g. OsPHO2) were significantly down-regulated by the antisense of OsSPX1. The microarray results were validated by real-time RT-PCR. Our study indicated that OsSPX1 may be involved in cross-talks between oxidative stress, cold stress and phosphate homeostasis in rice seedling leaves.